Tissue‐specific responses to aberrant FGF signaling in complex head phenotypes. Issue 3 (20th February 2013) - Martínez‐Abadías, Neus; Motch, Susan M.; Pankratz, Talia L.; Wang, Yingli; Aldridge, Kristina; Jabs, Ethylin Wang; Richtsmeier, Joan T.
<x xml:space="preserve">Abstract</x> COVER PHOTOGRAPH: Multimodal imaging and segmentation used to visualize skull (yellow), brain (pink), inner ear (green), nasopharynx (green) and globe of the eye (blue) in Fgfr2cC342Y/+Crouzon syndrome mice (top) and normal littermates (bottom). From Martínez‐Abadías et al., Developmental Dynamics 242:80–94, 2013.